Consumption Frequency of Foods Away from Home Linked with Higher Body Mass Index and Lower Fruit and Vegetable Intake among Adults: A Cross-Sectional Study. (26th January 2016) - Seguin, Rebecca A.; Aggarwal, Anju; Vermeylen, Francoise; Drewnowski, Adam
Abstract : Introduction . Consumption of foods prepared away from home (FAFH) has grown steadily since the 1970s. We examined the relationship between FAFH and body mass index (BMI) and fruit and vegetable (FV) consumption. Methods . Frequency of FAFH, daily FV intake, height and weight, and sociodemographic data were collected using a telephone survey in 2008-2009. Participants included a representative sample of 2, 001 adult men and women (mean age 54 ± 15 years) residing in King County, WA, with an analytical sample of 1, 570. Frequency of FAFH was categorized as 0-1, 2–4, or 5+ times per week. BMI was calculated from self-reported height and weight. We examined the relationship between FAFH with FV consumption and BMI using multivariate models. Results . Higher frequency of FAFH was associated with higher BMI, after adjusting for age, income, education, race, smoking, marital status, and physical activity (women: p = 0.001 ; men: p = 0.003 ). There was a negative association between frequency of FAFH and FV consumption. FAFH frequency was significantly (p < 0.001 ) higher among males than females (43.1% versus 54.0% eating out 0-1 meal per week, resp.). Females reported eating significantly (p < 0.001 ) more FV than males. Conclusion . Among adults, higher frequency of FAFH was related to higher BMI and less FV consumption.